Penerapan Arsitektur Biofilik pada Rumah Susun di Kecamatan Tallo - Puspitasari, Desi; Nursyam, Nursyam; Sutrisno, Mohammad (TIMPALAJA : Architecture Student Journals, 2025)
This research is motivated by the high population density in Tallo District, Makassar City, which triggers the development of slums and reduces the quality of the residential environment. The purpose of this research is to formulate the concept and design of a flat with a biophilic architecture approach as an alternative to relocating slum dwellers, making it more livable, healthy, and sustainable. The method used is a descriptive method, with three data collection techniques: a literature review on flats and biophilic architecture, a field survey to identify existing conditions and potential areas, and a precedent study of buildings that have implemented the biophilic concept as a design reference. The design results in the form of a multi-storey flat concept that combines 14 biophilic patterns and biophilic principles such as nature in the space, natural analogues, and nature of the space, which are realized through the application of vegetation on the balcony, natural lighting and ventilation arrangements, the use of biomorphic forms, natural textured materials, and the creation of a safe and comfortable space. The implementation of this concept is expected to reduce the area of slum settlements, improve the quality of green open spaces, and provide vertical housing that supports the physical and psychological health of residents, thereby enhancing the quality of the residential environment in Tallo District.